2007
DOI: 10.1002/pen.20815
|View full text |Cite
|
Sign up to set email alerts
|

Processability studies of silica‐thermoset polymer matrix nanocomposites

Abstract: The aim of this study is to investigate the processability of silica-thermoset polymer matrix nanocomposites in terms of dispersion of silica nanoparticles and their effect on curing. Two thermosetting resins were considered, an epoxy and a polyester resin, with 5 % silica, although 1% silica was also used in preliminary studies in the polyester system. Various combinations of mechanical mixing and sonication were investigated for the dispersion of silica nanoparticles under different processing conditions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Rheology DMTA tests in this study and DSC tests in a previous study 24 showed that silica nanoparticles promote the curing of epoxies and accelerate gelling. As a result, the mixture needs to be processed at lower temperatures in liquid composite moulding processes to extend the infiltration time.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Rheology DMTA tests in this study and DSC tests in a previous study 24 showed that silica nanoparticles promote the curing of epoxies and accelerate gelling. As a result, the mixture needs to be processed at lower temperatures in liquid composite moulding processes to extend the infiltration time.…”
Section: Discussionsupporting
confidence: 65%
“…The silica powder was dispersed in the epoxy resin in a solvent aided procedure to ensure homogeneous mixing, 24 where ethanol was the solvent employed. A suspension was produced with 10 g of WACKER HDK N20 powder in 120 mL ethanol and was sonicated in an ultrasonic bath at room temperature for 30 min to disperse the silica nanoparticles.…”
Section: Mixing and Rheology Of Silica-epoxy Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Dispersion of CNTs is most important to realise the benefits of the nano-effects [19,20]. For this reason, a solvent is frequently used as an aid for the dispersion at high shear [2,21]. Although the concept of multi-scale reinforcement in composite materials has been thought advantageous, on the basis of biocomposites such as bone, it is very difficult to fully infiltrate MWNTs through a continuous fibre reinforcement, following a feasible and cost-effective process.…”
Section: Introductionmentioning
confidence: 99%